Early repolarization in adolescent athletes: A gender comparison of ECG and echocardiographic characteristics - Vecchiato, M.; Baioccato, V.; Adami, P. E.; Quinto, G.; Foccardi, G.; Slanzi, G.; Battista, F.; Neunhaeuserer, D.; Ermolao, A. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Background The early repolarization pattern (ERp) is an electrocardiographic finding previously associated with arrhythmic risk in adults. The purpose of this study is to evaluate the prevalence and characteristics of ERp in a group of adolescent athletes according to gender. Furthermore, potential associations with clinical, electrocardiographic, and echocardiographic parameters are explored.